DEVELOPING A COMPUTER-BASED TESTING (CBT) METHOD FOR EFFECTIVE ASSESSMENT IN ISLAMIC EDUCATION: A CASE STUDY - Adhim, Fauzan; Acetylena, Sita; Afifin, Muhammad Odik; Anggarini, Ida Fitri (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: Innovation in learning evaluation systems is essential in response to the digital transformation within the field of education. This necessity also applies to Islamic Religious Education (PAI), which plays a strategic role in shaping students' religious character. However, the implementation of Computer-Based Testing (CBT) in Islamic-based educational institutions remains suboptimal. Purpose: This study aims to evaluate the effectiveness of CBT and analyze how students' perceptions of CBT correlate with their academic achievement in PAI at SMP Islam Sawahan Turen. Method: A quantitative approach with a descriptive-correlational design was employed. Closed-ended questionnaires and objective tests were used to measure students’ perceptions and obtain primary data. A stratified random sampling method was applied to select a sample of ninety students. All research instruments met statistical requirements based on validity and reliability tests. Data analysis revealed that students’ perceptions of CBT fell into the high category, with average scores across all items exceeding 4.00. Students also demonstrated strong cognitive performance, with an average PAI score of 78.44. Pearson correlation analysis indicated a positive and significant relationship between students’ perceptions of CBT and their academic achievement (r = 0.531; p < 0.05). Result: These findings suggest that CBT is an effective tool for evaluation and contributes to improved academic outcomes. Conclusion: This study supports the development of digital assessments aligned with PAI values and encourages the integration of technology in character-based education.